Ham radio for dummies - Silver, H. Ward (For Dummies, a Wiley Brand, 2018)
Ham radio, or amateur radio, is a way to talk with people around the world in real-time, or to send email without any sort of internet connection. It provides a way to keep in touch with friends and family, whether they are across town or across the country. It is also a very important emergency communication system. When cell phones, landlines, the internet, and other systems are down or overloaded, Amateur Radio still gets the message through. Radio amateurs, often called "hams," enjoy radio technology as a hobby, but are often called upon to provide vital service when regular communications systems fail. --Publisher